Edukasi Kepatuhan Minum Obat Penderita Stroke sebagai Pencegahan Komplikasi Stroke di Desa Dukuhwaluh - Amelia Sutantri; Adiratna Sekar Siwi; Suci Khasanah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Stroke is a serious neurological disorder with a high risk of disability and death. One of the main obstacles to recovery is low medication adherence due to lack of knowledge and forgetfulness. This community service program aims to improve the knowledge and adherence of stroke patients in Dukuhwaluh Village to prevent complications. The methods used included health education through lectures, videos, leaflets, and interactive discussions. Evaluation was conducted using the Morisky Medication Adherence Scale (MMAS) questionnaire and 28-day medication monitoring with family support. The results showed a significant improvement in knowledge. Before education, the "good" category was only 8%, but after the intervention, this jumped to 50%, and even reached the "very good" category at 25%. In terms of adherence, there was a drastic change from low adherence (42%) before the intervention to high adherence (100%) after the 28-day monitoring. In conclusion, health education accompanied by family involvement effectively improves medication adherence in stroke patients, thereby reducing the potential risk of complications and recurrent stroke.